Elevational range extension of Drab Water Tyrant, Ochthornis littoralis (Pelzeln, 1868) (Passeriformes, Tyrannidae) - Jefferson García-Loor (Check List, 2022)
The Drab Water Tyrant, Ochthornis littoralis (Pelzeln, 1868), is a small flycatcher occurring across lower Amazonia. Its usual habitat is the edges of rivers, and it is easily observed flying over sandbanks and among the trunks of fallen trees and branches. Here, I present a new locality in the Ecuadorian Andean foothills which represents a significant increase in this species’ elevational range from the Amazon lowlands. The new record is also from a previously unknown habitat for the species.